The Impact of Clustered Care on Itch Severity and Sleep Quality in Patients with Atopic Dermatitis via an Online Platform - Ruimin Wang; Cuimin Ren; Yanling Li; Bingshen Guo; Xiaoguang Zhang; Ling Wang; Liqian Luo; Yuying Zhang (Acta Dermato-Venereologica)
This study investigated the efficacy of clustered care delivered via an online platform for adult atopic dermatitis patients. Ninety-eight atopic dermatitis patients from the Second Hospital of Hebei Medical University (May 2022–May 2024) were randomly assigned to a study group (online clustered care) or a control group (routine care), with 49 in each. Outcomes, including itch severity (Visual Analogue Scale), atopic dermatitis severity (SCORAD), sleep quality (Pittsburgh Sleep Quality Index), and quality of life (Dermatology Life Quality Index), were assessed at baseline and 3 months post-intervention. After 3 ≈months, the study group showed significantly lower itch severity (p < 0.001), improved skin lesions, lesion area, and subjective symptoms (all p < 0.001), better sleep quality (p = 0.030), and enhanced quality of life (p < 0.001) compared with the control group. Clustered care through an online platform significantly reduces itch severity and improves sleep quality and overall disease management in atopic dermatitis patients, offering a promising clinical approach.